A framework for understanding the relation between spoken language input and outcomes for children with cochlear implants. (11th January 2022) - Houston, Derek M.
Abstract: Spoken language outcomes after cochlear implantation are highly variable. Some variance can be attributed to individual characteristics. Research with typically hearing children suggests that the amount of language directed to children may also play a role. However, several moderating factors may complicate the association between language input and language outcomes in children with cochlear implants. In this article, I present a conceptual framework that posits that the association between total language input directed to children and language outcomes is moderated by factors that influence what is accessible, attended to, and coordinated with the child. The framework also posits that children with cochlear implants exhibit more variability on those moderating factors, which explains why the relation between language input and language outcomes may be more complex even if language input is more important for successful language outcomes in this population.